2014
DOI: 10.1136/bmjopen-2013-003987
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up integrated prevention campaigns for global health: costs and cost-effectiveness in 70 countries

Abstract: ObjectiveThis study estimated the health impact, cost and cost-effectiveness of an integrated prevention campaign (IPC) focused on diarrhoea, malaria and HIV in 70 countries ranked by per capita disability-adjusted life-year (DALY) burden for the three diseases.MethodsWe constructed a deterministic cost-effectiveness model portraying an IPC combining counselling and testing, cotrimoxazole prophylaxis, referral to treatment and condom distribution for HIV prevention; bed nets for malaria prevention; and provisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…They related to cost-effectiveness, equity, harms, ethics, bottom-up/top-down scaling-up, and the context in which the EBI was scaled up (see Figure 2). To discuss them, we identified 45 scaling-up studies that raised these difficulties, of which 13 were on costeffectiveness estimates or cost-analysis models [22][23][24][25][26][27][28][29][30][31][32][33][34], 14 on equity [35][36][37][38][39][40][41][42][43][44][45][46][47][48], four on harms [16,[49][50][51][52], three on ethics [53][54][55], six on top-down implementation [42,[56][57][58][59][60], and eight on contextual problems [40,43,[61][62][63][64]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They related to cost-effectiveness, equity, harms, ethics, bottom-up/top-down scaling-up, and the context in which the EBI was scaled up (see Figure 2). To discuss them, we identified 45 scaling-up studies that raised these difficulties, of which 13 were on costeffectiveness estimates or cost-analysis models [22][23][24][25][26][27][28][29][30][31][32][33][34], 14 on equity [35][36][37][38][39][40][41][42][43][44][45][46][47][48], four on harms [16,[49][50][51][52], three on ethics [53][54][55], six on top-down implementation [42,[56][57][58][59][60], and eight on contextual problems [40,43,[61][62][63][64]…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness estimates need to consider the size of the targeted population, the incidence or prevalence of the disease or risk factor, the significance of the intervention's efficacy, and the amount spent or available [29]. Thus while many modelling studies show scalingup EBIs to be cost-effective [22][23][24]26,27,[30][31][32][33][34], they may not reflect the multi-factorial complexity of the real world. Categorical universal statements about the cost-effectiveness of scaling-up are thus difficult to justify.…”
Section: Introductionmentioning
confidence: 99%
“…Besides social media campaigns, traditional mass media campaigns have been shown to be a cost-effective tool in reducing the disease burden, especially in resourcepoor countries [20] . However, the recent urologic mass media campaign 'blood in pee' has not led to a significant change in the diagnosis of targeted cancers across a large catchment [21] .…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 A cost-effectiveness study comparing strategies for cervical cancer screening across five low-and middle-income countries found that strategies requiring fewer visits were also more efficient. 11,12 CHCs may similarly be an effective strategy to deliver cervical cancer screening rates in high-burden communities because of high capacity and proximity to residential areas. 11,12 CHCs may similarly be an effective strategy to deliver cervical cancer screening rates in high-burden communities because of high capacity and proximity to residential areas.…”
mentioning
confidence: 99%
“…10 The community-based health fair, or community health campaigns (CHCs), is an effective and cost-effective strategy to deliver screening and preventive health services in low-resource contexts. 11,12 CHCs may similarly be an effective strategy to deliver cervical cancer screening rates in high-burden communities because of high capacity and proximity to residential areas.…”
mentioning
confidence: 99%